RECEPTIVE AND PRODUCTIVE VOCABULARY ACQUISITION: EXAMINING PROCESSING TIME AND MEMORY THRESHOLD - Oberg, Andrew (Indonesian Journal of Applied Linguistics, 2012)
Abstract: In the present research a picture card-based vocabulary study method was used to determine the pace of learner acquisition in terms of both receptive and productive knowledge. Fifty-eight first-year Japanese university students in two classes were used in the study. The subjects were placed into a single experimental group and both classes were taught by the researcher. During the treatment sessions the subjects studied fifteen vocabulary items chosen from the course textbook (Fifty-Fifty: A speaking and listening course, Book One, W. Wilson and R. Barnard, 2007, Hong Kong: Pearson Longman) using self-produced picture cards. The same post-treatment test was given to the subjects following each treatment session and the results were analyzed using Paired Samples T-tests supported by non-parametric Wilcoxon matched pairs signed ranks tests by comparing one sessionâ€™s data with the data of the previous session. The post-treatment data showed a significant difference between the pre-treatment and first sessions in terms of receptive knowledge, and between all sessions except the eighth and ninth in terms of productive knowledge. Â  Keywords: Vocabulary learning; receptive knowledge; productive knowledge; processing time; memory threshold